NOVEL STEROLS OF THE TOXIC DINOFLAGELLATE KARENIA BREVIS (DINOPHYCEAE) A DEFENSIVE FUNCTION FOR UNUSUAL MARINE STEROLS?1 - Giner, José-Luis (Journal of phycology, 2003)
The "red tide" organism Karenia brevis (Davis) Hansen & Moestrup (=Gymnodinium breve Davis) produces a mixture of brevetoxins, potent neurotoxins responsible for neurotoxic shellfish poisoning in humans and massive fish kills in the Gulf of Mexico and the southern Atlantic coast of the United States. The sterol composition of K. brevis was found to be a mixture of six novel and rare Δ8(14) sterols. The two predominant sterols, (24R)-4α-methylergosta-8(14), 22-dienol and (24R)-4α-methyl-27-norergosta-8(14), 22-dienol, were named gymnodinosterol and brevesterol and represent potentially useful biomarkers for K. brevis. A possible function for such unusual marine sterols is proposed whereby structural modifications render the sterols non-nutritious to marine invertebrates, reducing predation and thereby enhancing the ability of the dinoflagellates to form massive blooms